Arbitrability Restrictions in Action - England, G.; McKenna, I. (Relations industrielles / Industrial Relations, 1992)
The authors test a number of hypotheses as to the possible impact on the collective bargaining process of section 48 of the Alberta Public Service Employee Relations Act which declares non-arbitrable a broad range of management rights items. This study compares the collective bargaining relationship for two units of hospital workers and examines the Crown Service sector.